Seawater electrolysis technologies for green hydrogen production: challenges and opportunities. (June 2022) - Gao, Fei-Yue; Yu, Peng-Cheng; Gao, Min-Rui
Abstract : Green hydrogen (H2 ) as a sustainable energy carrier can be directly produced through water electrolysis, potentially replacing traditional fossil fuels to achieve carbon neutrality. Current water electrolysis technologies rely on ultrapure freshwater, which, however, is scarce (<1% of earth's water) and unevenly distributed around the world. Due to the abundant reserves and reasonable economic feasibility, the conversion of seawater to H2 powered by renewable electricity is considered as a promising candidate toward energy sustainability. Recently, the mechanism of seawater electrolysis has been progressively clarified, motivating the development of design principles, for example, the alkaline design criteria and the Cl – blocking layer, for improved catalyst performance. We discuss the vital aspects of seawater electrolysis, including the challenges and recent development in electrode materials. We outline potential strategies that enable highly active and selective catalysts for seawater electrolysis in the presence of contaminants such as metal ions, chloride, and bio-organisms, as well as describe issues in electrolyzer design. This perspective is concluded by presenting several development opportunities to advance this promising technique.